Twist regulates Yorkie activity to guide lineage reprogramming of syncytial alary muscles - Rose, Marcel; Domsch, Katrin; Bartle-Schultheis, Jakob; Reim, Ingolf; Schaub, Christoph (Cell reports, 2022)
Genesis of syncytial muscles is typically considered as a paradigm for an irreversible developmental process. Notably, transdifferentiation of syncytial muscles is naturally occurring during Drosophila development. The ventral longitudinal heart-associated musculature (VLM) arises by a unique mechanism that revokes differentiation states of so-called alary muscles and comprises at least two distinct steps: syncytial muscle cell fragmentation into single myoblasts and successive reprogramming into founder cells that orchestrate de novo fiber formation of the VLM lineage. Here, we provide evidence that the mesodermal master regulator twist plays a key role during this reprogramming process. Acting downstream of Drosophila Tbx1 (Org-1), Twist is regulating the activity of the Hippo pathway effector Yorkie and is required for the initiation of syncytial muscle dedifferentiation and fragmentation. Subsequently, fibroblast growth factor receptor (FGFR)-Ras-mitogen-activated protein kinase (MAPK) signaling in resulting mononucleated myoblasts maintains Twist expression, thereby stabilizing nuclear Yorkie activity and inducing their lineage switch into founder cells of the VLM.
Gesehen am 02.03.2022